Missiological response to the effects of Boko Haram insurgency in Northern Nigeria - Akinyemi O. Alawode (HTS Teologiese Studies/Theological Studies)
Since the emergence of Boko Haram in Nigeria, the country has witnessed diverse forms of violence, terrorism attacks, kidnapping and banditry, among others. The activities of Boko Haram have led to the loss of lives and properties, and displacement of people from their ancestral homes. People have lost their source of livelihood, family members and loved ones. This article provides the church’s response to the insurgency activities of Boko Haram in Nigeria from a missiological perspective. The study adopted the descriptive research design to gather the needed information. The primary data were gathered through interviews with some identified pastors currently serving in Northern Nigeria. Moreover, secondary data were gathered from books and journals about the examined topic. The effects of the insurgency, as discussed in the article, are socio-political, educational, economic and religious.